A systematic review and network meta-analysis of the efficacy and safety of third-line and over third-line therapy after imatinib and TKI resistance in advanced gastrointestinal stromal tumor - Xiao, Xianhao; Yuan, Weiye; Wang, Chong; Song, He (Frontiers in Pharmacology, 2022)
Abstract Tyrosine kinase inhibitors (TKIs) has greatly improved the prognosis of unresectable and metastatic gastrointestinal stromal tumors (GISTs) in the last two decades. Imatinib and sunitinib have been recommended as the first-line and second-line therapies, respectively. However, there is still lack of precision therapy for refractory GISTs in terms of therapy after imatinib and sunitinib. We searched electronic databases, including PubMed, EMBASE, Web of Science Cochrane Library, and ClinicalTrials, comprehensively from inception to October, 2022. Randomized controlled trials featuring comparisons with third-line or over third-line therapy against GISTs were eligible. The primary outcome was the progression-free survival (PFS). All the network calculations were performed using random effect models, and the ranking of regimens were numerically based on the surface under the cumulative ranking (SUCRA) statistics. A total of 7 studies were eligible for inclusion in this network meta-analysis. After analysis, ripretinib ranked top in progression free survival (PFS), overall survival (OS), and Disease Control Rate (DCR) (SUCRA statistics: 83.1%, 82.5%, and 86.5%, respectively), whereas nilotinib and pimitespib presented better tolerability (SUCRA statistics: 64.9% and 63.8%, respectively). We found that regorafenib still seemed to be more reliable for clinical administration, and ripretinib shows good effectiveness for the over third-line therapy. Precise targeted therapy is a very important direction for the future treatment of GIST, and more high-quality studies of new agents were expected.